2011
DOI: 10.1155/2011/368692
|View full text |Cite
|
Sign up to set email alerts
|

In VitroandIn VivoAntimalarial Activity Assays of Seeds fromBalanites aegyptiaca: Compounds of the Extract Show Growth Inhibition and Activity against Plasmodial Aminopeptidase

Abstract: Balanites aegyptiaca (Balanitaceae) is a widely grown desert plant with multiuse potential. In the present paper, a crude extract from B. aegyptiaca seeds equivalent to a ratio of 1 : 2000 seeds to the extract was screened for antiplasmodial activity. The determined IC50 value for the chloroquine-susceptible Plasmodium falciparum NF54 strain was 68.26 μg/μL ± 3.5. Analysis of the extract by gas chromatography-mass spectrometry detected 6-phenyl-2(H)-1,2,4-triazin-5-one oxime, an inhibitor of the parasitic M18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 21 publications
0
24
1
1
Order By: Relevance
“…Studies have shown that asymptomatic malaria increases with age as pre-immunity gradually develops [36], and that the use of ITNs is a reliable malaria preventive measure [37]. In contrast, the prevalence in the present study was lower than the 43.7% reported in western Kenya [38] and could be partly attributed to consumption of herbs, as 10.9% of the subjects who participated in the present study consumed herbs that may have antiplasmodial activities [39]. In addition, almajirai's lifestyle exposes them to many hardships, including infections [25]; thus, they could have experienced sufficient malaria episodes resulting in preimmunity even at an early age.…”
Section: Discussioncontrasting
confidence: 84%
“…Studies have shown that asymptomatic malaria increases with age as pre-immunity gradually develops [36], and that the use of ITNs is a reliable malaria preventive measure [37]. In contrast, the prevalence in the present study was lower than the 43.7% reported in western Kenya [38] and could be partly attributed to consumption of herbs, as 10.9% of the subjects who participated in the present study consumed herbs that may have antiplasmodial activities [39]. In addition, almajirai's lifestyle exposes them to many hardships, including infections [25]; thus, they could have experienced sufficient malaria episodes resulting in preimmunity even at an early age.…”
Section: Discussioncontrasting
confidence: 84%
“…2,4 DTBP has been reported to be present in fruits as well as seeds and imparts antioxidant properties (Choi et al, 2013). This volatile phenolic compound is reported to have in vitro antimalarial activity where the plasmodial growth was arrested with an amount of 100 mM compound (Kusch et al, 2011). One recent report indicates the presence of 2,4 DTBP in the culture filtrate (CF) of an antifungal Lactobacillus strain where the compound was detected by GC-MS analysis (Sangmanee and Hongpattarakere, 2014).…”
Section: Purification and Characterizationmentioning
confidence: 99%
“…Table 3 showed that this extract could inhibit the plasmodium. It was assumed that phenol, tannin and triterpenoid in this extract could inhibit the para- Kusch et al (2011) who explained that phenol increase cellular oxidation in red blood cell and inhibit protein synthesis of parasite when act as antimalarial agent. Builder (2010) taked that these processes will lead to oxidative damage by malaria parasite induction.…”
Section: Resultsmentioning
confidence: 99%